PENGARUH KONDISI KEUANGAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN (Studi Kasus pada Perusahaan Pertambangan Subsektor Industri Batu Bara di Bursa Efek Indonesia Tahun 2015 - 2018) - Maretta, Anis Lila; Rispantyo, Rispantyo; Kristianto, Djoko (Universitas Slamet Riyadi, 2020)
A going concern audit opinion is an unqualified audit opinion with an explanatory paragraph that contains a great deal of doubt about the sustainability of the company's business. The purpose of this study is to determine (1) The effect of financial conditions on going concern audit opinion (2) The effect of company size on going concern audit opinion. This study uses secondary data in the form of audited financial statements originating from the Indonesia Stock Exchange (IDX). The population in this study is the coal industry subsector mining company during the 2015 - 2018 observation period. The sampling technique in this study used a purposive sampling method. Data analysis techniques used in this study were descriptive analysis, logistic regression analysis test, overall model test, coefficient of determination and hypothesis testing (F test and T test). Based on the results of data analysis the influence of the company's financial condition on going concern audit opinion obtained a negative coefficient and significant effect. The effect of company size on going concern audit opinion obtained positive coefficient and no effect. Suggestions in this study are to expand the object of research on mining companies on the Stock Exchange, use a longer span of research and add variables in subsequent research.